2001
DOI: 10.1074/jbc.m103902200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Characterization of Chicken Toll-like Receptors

Abstract: Toll-like receptors (TLR) in the innate immune system have not been identified in non-mammalian vertebrates. Two types of TLR were cloned from a chicken bursa cDNA library using degenerate primers based on the consensus sequences of mouse and Drosophila Toll and designated as chicken TLR (chTLR) type 1 and type 2. Of the nine human TLRs reported to date, these chTLRs showed the highest homology to human TLR2. The extracellular regions of type 1 and type 2 contained a distinct ϳ200-amino acid stretch and were 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 42 publications
2
106
1
Order By: Relevance
“…5). We first confirmed that the chTLRs function in the human system using human HEK293 cells as reported previously (4). A single TLR member of the chTLR2 subfamily alone had no ability to induce luciferase activity in response to PGN, Malp-2 or Pam3.…”
Section: Results and Dicussionsupporting
confidence: 85%
See 3 more Smart Citations
“…5). We first confirmed that the chTLRs function in the human system using human HEK293 cells as reported previously (4). A single TLR member of the chTLR2 subfamily alone had no ability to induce luciferase activity in response to PGN, Malp-2 or Pam3.…”
Section: Results and Dicussionsupporting
confidence: 85%
“…This subfamily of TLRs appears to have advanced as a pattern recognition receptor in conformity with principles of evolution. We had identified chTLR2 type1 and chTLR2 type2 earlier than the chicken genome information was published (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prior to our work, it was demonstrated that ChTLR2 is functional when expressed in the human HEK293 cell line. 3 Our own experiments unambigu ously showed that ChTLR3 is active in HEK293 cells and that it exclusively recognizes dsRNA, like its mammalian counter part.…”
Section: Discussionmentioning
confidence: 99%